Fungsi Pertahanan Ego Cinderella terhadap Penindasan Keluarga Tiri dalam Film Cinderella Produksi Walt Disney (1950) - Putri Sulastri (Universitas Palan, 2026)
This study aims to analyze the ego defense functions used by the character Cinderella in facing oppression perpetrated by her stepmother and stepsisters in the Walt Disney film Cinderella (1950). This study uses a descriptive qualitative approach, namely an approach that focuses on depicting phenomena in depth and systematically. Research data were obtained through analysis of dialogue, storyline, and the behavior of the main character relevant to the focus of the study. The analysis was conducted with reference to Sigmund Freud's psychoanalytic theory, particularly the concept of ego defense mechanisms as a form of individual response to psychological stress. The results of the study indicate that the character Cinderella uses five types of ego defense mechanisms in facing conflict and emotional stress, namely repression, denial, displacement, rationalization, and reaction formation. These ego defense mechanisms play an important role in helping Cinderella maintain emotional stability, manage psychological suffering, and maintain a positive attitude amidst the oppressive situation she experiences.